Oral contraceptive use in women at increased risk of breast/ovarian cancer: knowledge and attitudes. Issue 1 (9th September 2011) - Bui, Kim Tam; Wakefield, Claire E.; Kasparian, Nadine A.; Tyler, Janet; Abbott, Jason; Tucker, Kathy
Abstract Background Several of the health benefits and risks associated with the combined oral contraceptive pill (COCP) are particularly relevant to women at risk of hereditary breast and/or ovarian cancer. Methods Eighty‐three past female patients of an Australian hereditary cancer clinic aged 18–50 years completed a self‐report questionnaire to assess their contraceptive practices, knowledge and information needs (44% response rate). Results Ninety‐two percent of participants had previously used the COCP, with a mean knowledge score of 3.63 out of 8. Nearly 40% reported that their family history of cancer was one reason they discontinued/avoided using the COCP. Women reported receiving insufficient COCP information and preferred a targeted information leaflet to answer their questions. Conclusions Although recall bias may have affected some women, there is a clear need to improve the consistency of information delivered to women at risk of hereditary breast and/or ovarian cancer, to ensure informed contraceptive choices are made. Copyright © 2011 John Wiley & Sons, Ltd.